What you have in your answer is:
sqrt(4/3) and that is the same as sqrt4/sqrt3
But, you should not have a sqrt on the denominator (a stylistic thing).
So what you do to remove the root is multiply the fraction sqrt4/sqrt3 by sqrt3/sqrt3 (essentially you are multiplying by one because the numerator=denominator)
So by multiplying by sqrt3/sqrt3 you get [(sqrt4)(sqrt3)] / [(sqrt3)(sqrt3)]
So simplify the denominator to 2 * sqrt3
Simplify the denominator to 3.
Your answer is (2 * sqrt3)/3
2007-05-20 08:46:03
·
answer #1
·
answered by dust25 2
·
1⤊
0⤋
3.x² = 4
x ² = 4 / 3
x = ± 2 / √3
x = ± 2.√3 / 3
2007-05-20 08:40:13
·
answer #2
·
answered by Como 7
·
0⤊
0⤋
You need to rationalize the denominator. The 4 and 3 both have squareroots on them. Squareroot of 4 is 2 because 2 times 2 is for. But you have to get rid of the squareroot of 3...
2007-05-20 08:37:53
·
answer #3
·
answered by Jaguar88 2
·
0⤊
0⤋
You are right, you just didn't rationalize the denominator:
√(4/3) = 2√(1/3) = (2√(3))/3
2007-05-20 08:41:05
·
answer #4
·
answered by hawkeye3772 4
·
0⤊
0⤋
sqrt(4/3) = 2/sqrt(3) = 2 * sqrt(3) / 3
They're equivalent answers, really.
2007-05-20 08:39:02
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
4-3x^2=0
-4 -4
-3x^2=-4
_______
-3
square root (x^2=4/3)
x=1.1547
Hope this helped!
2007-05-20 08:44:49
·
answer #6
·
answered by Tom Mienic 3
·
0⤊
0⤋
you are not wrong..
the square root of (4/3) is 2/3 root 3....plus or minus of course, which is your answers, just rationalized..
2007-05-20 08:41:39
·
answer #7
·
answered by JAC 3
·
0⤊
0⤋
you cant have a square root on the bottom of the fraction
2007-05-20 08:55:25
·
answer #8
·
answered by davidred15 2
·
0⤊
0⤋
october 26th
2007-05-20 08:39:32
·
answer #9
·
answered by Anonymous
·
1⤊
0⤋